Intra-household nutrient distribution and adequacy of food and nutrient intake of urban households - Aligaen, Melba B. 1951-; Florencio, Cecilia A. (1978)
One hundred households in the Metropolitan Manila Area were studied to determine the adequacy of their food and nutrient intake and to examine the distribution of nutrients within the household. Food intake data of individual respondents for two days were gathered utilizing the methods of food weighing and food recall. Socio-economic characteristics of the household relevant to food consumption were identified by means of the questionnaire-interview method. The survey population totaling 474 members was composed of 83 household heads, 94 housewives and 297 offspring. In the analysis of nutrient distribution within the household, offspring were further classified into sex, age, and sex-age groupings. Of the total per capita food intake of 545.4 grams per day, more than half came from cereals and cereal products from cereals and cereal products and fish, meat and poultry. When compared with the Recommended Dietary Allowance (RDA), only the food group fish, meat and poultry was found sufficient in the diet. The food intake of the respondents was inadequate in calories and in the eight nutrients considered, except iron. The per capita calorie and protein intakes were 73.6 percent and 90.2 percent of the RDA, respectively. The least adequately met nutrient in their diet was vitamin A. In addition to an overall inadequacy in the food and nutrient intake of household members, the results also showed inequality in the intra-household distribution of nutrients. On the the basis of sex, household heads and male offspring had more adequate diets than housewives and female offspring, respectively. On the basis of age, preschoolers had a better nutrient intake among all the categories of offspring while the adolescents had the poorest nutrient consumption. When compared with household heads, offspring, except for the preschoolers, consumed less adequate diets. On the basis of both sex and age, male preschoolers were the most adequately fed group, while the male and female adolescents were least adequately provided for.
Appendices: leaves 118-161.
Mimeographed.
Thesis (M.S.)--University of the Philippines, Quezon City.
Vita.
Keywords: Nutrition surveys -- Philippines -- Manila metropolitan area; Diet -- Philippines -- Manila metropolitan area